2015
DOI: 10.1159/000381921
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Cryo-Transbronchial Biopsy in Diffuse Lung Diseases: Analysis of Three Hundred Cases

Abstract: Background: Transbronchial biopsy (TBB) which is performed with metal forceps (forceps TBB) has been accepted as a useful technique in establishing diagnoses of diffuse lung diseases (DLDs). The use of cryoprobes to obtain alveolar tissue (cryo-TBB) is a new method which is currently used by our institute as well as others with excellent results. Objectives: To assess the safety of cryo-TBB compared with conventional forceps TBB. Methods: We performed a retrospective data evaluation of 300 consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 29 publications
(41 reference statements)
6
34
0
1
Order By: Relevance
“…case reports, review articles); the remaining 37 articles were retrieved for detailed full-text evaluation. Eighteen original studies were included in the present review, and their main characteristics are presented in table 3[7,8,9,19,20,21,22,23,24,25,26,27,28,29,30,31,32]: 15 studies reported data on both DY and safety, 2 on safety only, and 1 on DY only. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…case reports, review articles); the remaining 37 articles were retrieved for detailed full-text evaluation. Eighteen original studies were included in the present review, and their main characteristics are presented in table 3[7,8,9,19,20,21,22,23,24,25,26,27,28,29,30,31,32]: 15 studies reported data on both DY and safety, 2 on safety only, and 1 on DY only. …”
Section: Resultsmentioning
confidence: 99%
“…The pooled estimate of 0.12, presented in figure 6, should be interpreted with caution, as the definition of ‘moderate' bleeding was vastly different between the studies, making a reliable summary of the data difficult to accomplish. Moreover, the largest cohort studies were not included in this analysis, since Gershman et al [27] did not distinguish between mild and moderate bleeding (overall rate 5.3%), while the preventive use of a Fogarty balloon in our study was considered a major ‘bias' in the interpretation of the results. Anyhow, the fact that we did not experience any grade 2 bleeding does not mean that this is not a common and potentially serious adverse event related to the procedure; it rather suggests that using a prophylactic bronchial blocker is highly recommended in order to reduce and limit such a complication.…”
Section: Discussionmentioning
confidence: 99%
“…1). 27,[37][38][39][40][41][42][43][44][45][46][47][48][49] Nine studies were retrospective, 27 39,41 one in immunocompromised subjects with pulmonary infiltrates, 38 and one including subjects from all 3 categories 46 (Table 1). The studies were generally of good quality (Table 2), with the median (interquartile range) QualSyst score being 18 (17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
“…Severe bleeding (requiring either cessation of the procedure or the use of a bronchial blocker/sealant or surgical 27 Pajares et al 37 Fruchter et al 38 Fruchter et al 39 Kropski et al 40 Yarmus et al 41 Casoni et al 42 Fruchter et al 43 Griff et al 44 Pajares et al 45 Gershman et al 46 Hagmeyer et al 47 Hernández-González et al 48 Pourabdollah et al 49 1. Question/objective sufficiently described ?…”
Section: Discussionmentioning
confidence: 99%
“…In some articles, the safety profile is comparable to that of the conventional biopsy forceps, but a higher rate of pneumothoraces and severe haemorrhage has also been described with this technique [3,4,11]. Pajares et al [4], in a randomized trial comparing cryoprobes and forceps in patients with interstitial lung diseases inconsistent with usual interstitial pneumonia, found a higher diagnostic yield in the cryobiopsy group, even after histological findings had been submitted to a multidisciplinary approach.…”
mentioning
confidence: 99%